(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The purpose of this study is to ascertain the perceptions of prospective teachers about tolerance education. This research is a descriptive, qualitative study. A semi-structured and non- directive interview technique is used for collecting data. Research is carried out with 30 prospective teachers who attend Singhania University University Faculty of Education during the 2009 to 2010 academic years. Each participant is interviewed on the basis of their own will. Random sampling is used for this study. The results of the research reveal that prospective teachers are aware of the need for tolerance and tolerance education, both in society and within educational systems. In such, they make suggestions in parallel with this need. It is found that participants reveal views similar to those expressed within academic studies on the subject in their descriptions and suggestions regarding the need for tolerance in society and within the educational system.